A OFERTA E A DEMANDA DE PEDAGOGOS NO PARANÁ (2009-2013): ANÁLISE DA RELAÇÃO ENTRE TRABALHO E FORMAÇÃO E SUAS IMPLICAÇÕES NA (DES) VALORIZAÇÃO PROFISSIONAL - Vaz, Marta Rosani Taras (2016)
This research had as main objective to analyze of the relationship between supply and demand for pedagogue, in the state of Paraná. This study, besides, It aims to understand the relation between work and training in capitalism, as well, as the process of valorization (or devaluation) of the professionals of Pedagogy. This research analyzes dialectically the relations between capital and work, with the aim of observing the mediation of vocational training policies of educators in the current form of sociability. The study starts from the methodological and theoretical assumptions of historical dialectical materialism, which encompass the ontological conception of work and entering the historical dimension of capitalism. Statistical data were collected on the site of the National Institute of Educational Studies and Research Anísio Teixeira (INEP) in the State Department of Education of Paraná site (SEED-PR), as regards the demand for teaching duties in 2009 to 2013. in addition, there was the collection of quantitative data provided by 37 higher education institutions (HEI) of 122 that offer the Faculty of Education in Paraná, on the number of graduates in Education in the state, in the period analyzed. This research revealed, from the praxis (the theoretical and empirical analysis), we have had a greater offer of educators in the last years, both national and state (Paraná) levels in relation to the increase of demand of these professionals by labor market, because, in the analyzed period, an increase of 16,187 functions in Paraná, and 26,518 people completed the Faculty of Education in the state, the educational institutions that publish their data. We conclude, therefore, that this disproportion between supply and demand generates surplus population of teachers, which contributes to the devaluation of the teacher in the state of Paraná. This tendency is current and also, a manifestation that comes from the logic of capital and from the bourgeoisie social organization, and results in deregulation and devaluation of work, in which, In this sense, the complete overcoming of the devaluation and commercialization of the human workforce only will be viable with the overcoming of the capitalist society, as well as the defense of the generalization of professional training at higher education will be possible only on the side of the workers struggle, not only by the struggle for rights and labor appreciation, but the struggle for overcoming the salaried work and the consolidation of associated work.